Necrotizing enterocolitis. Controlled study of 3 years' experience in a neonatal intensive care unit. Issue 10 (October 1977) - Bunton, G L; Durbin, G M; McIntosh, N; Shaw, D G; Taghizadeh, A; Reynolds, E O; Rivers, R P; Urman, G
Abstract : During the 3 years 1972-74, 17 infants were treated for necrotizing enterocolitis (NEC) in the Neonatal Unit at University College Hospital. The incidence of the illness was 0.2% of live births in the hospital and 2.7% of those referred from elsewhere. The mean birthweight of the affected infants was 1832 g (range 878-3850 g) and mean gestational age 33 weeks (range 28-40 weeks). The illness was diagnosed at a mean age of 16 days (range 3-33 days). 14 infants (82%) survived. One infant developed NEC because of a volvulus, and another because of an apparently abnormal arterial supply to a segment of bowel. Each of the remaining 15 infants was matched with 3 control infants in order to see whether any factors predisposing to the development of NEC could be identified. Birth asphysia, the use of umbilical catheters, the length of time that these catheters were in place, and complications of catheterization were all significantly more frequent in the infants who developed NEC than in the controls. These findings support the view that hypoxia and ischaemia of the gut wall are important in the pathogenesis of NEC.